Bioactives Actinomycetes of marine sediment from the central coast of Peru - León, Jorge (2007)
In the present research we evaluated the antibacterial and antifungical activity of marine actinomycetes over pathogen of clinical origin. Likewise, it was evaluated the capacity to produce extracellular enzymes like carbohidrases, lipases and proteases. The Actinomycetes were isolated from sediments collected between September to December 2005 of Ancón (Lima) and Independencia (Ica) Bays at depths of 34 and 100 m. The isolation was performed in Casein - Starch Agar (CSA) and Marine Agar (AM) with addition of Cicloheximide (10 μg/mL). The antimicrobial evaluations were done comparing them with pathogenic antibiotic-multiresistant bacteria and fungi from clinical origin; in as much, to evaluate their multienzimatic activity several polimeric substrates were used. A total of 62 actinomycetes were isolated, 31 of there (50%) showed antibacterial activity in opposite to Staphylococcus aureus, 36 (59%) in opposite to Pseudomonas aeruginosa and 23 (37%) to both pathogens. Strains of actinomycetes I-400A and M10-77 identified in each case like Streptomyces and Thermoactinomyces exhibited higher inhibitory activity against S. aureus and P. aeruginosa respectively. Also, 13 actinomycetes (20,97%) showed to antifungical activity against cultures of Candida albicans strain 1511 and 17 (27,42%) with Candida albicans strain 1511MIC; nevertheless, no actinomycete displayed inhibitory activity to the growth of Aspergillus niger, Aspergillus fumigatus and Trichophyton mentagrophytes. Most Actinomycetes showed to have multienzymic activity able to hydrolysis polymerics compounds like the tween-80 (96%), gelatin (95%), starch (93%), lecitine (88%) and casein (74%). Extracts of the active compound obtained from the strain M10-77 with ethyl acetate produced a notable inhibitory activity against S. aureus. We conclude that the marine sediment is source of Actinomycetes with great capacity to produce bioactives substances of medical-pharmacological and industrial relevance.